2017
DOI: 10.1111/desc.12532
|View full text |Cite
|
Sign up to set email alerts
|

Around the world, adolescence is a time of heightened sensation seeking and immature self‐regulation

Abstract: Thedualsystemsmodelofadolescentrisk-takingportraystheperiodasonecharacterized by a combination of heightened sensation seeking and still-maturing selfregulation,butmosttestsofthismodelhavebeenconductedintheUnitedStatesor Western Europe. In the present study, these propositions are tested in an internationalsampleofmorethan5000individualsbetweenages10and30yearsfrom11 countriesinAfrica,Asia,EuropeandtheAmericas,usingamulti-methodtestbattery thatincludesbothself-reportandperformance-basedmeasuresofbothconstructs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
226
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(246 citation statements)
references
References 46 publications
14
226
0
6
Order By: Relevance
“…These data support the hypothesis that early adolescents show less efficient (or less strategic) risk taking (i.e., relatively more exploded balloons), which transforms into a more optimal form of risk taking in late adolescence, as evidenced by relatively larger payoffs (Crone, van Duijvenvoorde, & Peper, ). These findings are consistent with other studies that have suggested a rise in risk‐taking behavior from childhood to midadolescence, especially for “hot” risk‐taking tasks that include affective components of decision making (Burnett et al., ; Figner et al., ; Steinberg et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…These data support the hypothesis that early adolescents show less efficient (or less strategic) risk taking (i.e., relatively more exploded balloons), which transforms into a more optimal form of risk taking in late adolescence, as evidenced by relatively larger payoffs (Crone, van Duijvenvoorde, & Peper, ). These findings are consistent with other studies that have suggested a rise in risk‐taking behavior from childhood to midadolescence, especially for “hot” risk‐taking tasks that include affective components of decision making (Burnett et al., ; Figner et al., ; Steinberg et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, two contrasting developmental patterns characterize adolescence (64,65). On some measures, such as cognitive control, and self-regulation, there is a relatively linear trajectory from childhood through adolescence to adulthood.…”
Section: Continuous Knowledge Acquisition Vs Discontinuous Developmementioning
confidence: 99%
“…During adolescence, youth experience transitions and stressors that often threaten their subjective well‐being (Gilman & Huebner, ; Steinberg et al, ). Specifically, youth experience less life‐satisfaction and more depressed mood during early to mid‐adolescence (Goldbeck, Schmitz, Besier, Herschbach, & Henrich, ; Natsuaki, Biehl, & Ge, ).…”
Section: Optimism and Adolescent Well‐beingmentioning
confidence: 99%